2008
DOI: 10.1111/j.1600-9657.2008.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of tooth injuries in patients treated in hospital environment in the region of Araçatuba, Brazil during a 6‐year period

Abstract: Dental trauma has been considered as a public health problem that affects mainly children and youngsters and due to its impact on the patient's quality of life. This study presents the results of a 6-year survey of the occurrence and characteristics of dental trauma in patients admitted to the Service of Surgery and Oral and Maxillofacial Traumatology of the School of Dentistry of Araçatuba (UNESP, Brazil) after emergency care in hospital facilities in the region of Araçatuba, SP, Brazil. For such purpose, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 21 publications
5
40
2
9
Order By: Relevance
“…In the present study, the cause most reported by students suffering dental trauma was fall (42.86%), followed by collision with objects or people (27.38%), corroborating the aforementioned studies [2,18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the cause most reported by students suffering dental trauma was fall (42.86%), followed by collision with objects or people (27.38%), corroborating the aforementioned studies [2,18].…”
Section: Discussionsupporting
confidence: 91%
“…According to several authors [2,18] the most common causes of TDIs are falls or collisions with objects or people. In the present study, the cause most reported by students suffering dental trauma was fall (42.86%), followed by collision with objects or people (27.38%), corroborating the aforementioned studies [2,18].…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao sexo, a maioria dos estudos mostrou que as crianças do sexo masculino sofrem, significativamente, mais injúrias traumáticas nos dentes do que as crianças do sexo feminino 3,7,10,24,25,27,29,31,32,34,39,45,46,50,51,[53][54][55][56][57][58][59][60][61] .…”
unclassified
“…Neste estudo, também se observou que, com relação ao conhecimento sobre o atendimento do TD, melhor capacitação deve ser oferecida tanto para os cirurgiões dentistas quanto para outros profissionais, como cuidadores e educadores, frequentemente presentes no momento do traumatismo dentário [15][16][17][18][19] . Segundo diversos autores 14,[52][53][54][58][59][60][65][66][67][68] , as causas mais comuns do TD são as quedas ou colisões com outras pessoas. Todavia a crença de que resulta de "acidentes" ou "eventos aleatórios" tem contribuído para que o evento e sua prevenção sejam negligenciados.…”
unclassified
“…Authors also observed the high prevalence of falls and sports traumas in both developed and developing countries 10 . In Brazil, the conducted studies presented some limitations: (a) evaluation of a specific population, like children 11 or rural population; 8 (b) evaluation of fractures and the required treatment only; 12 (c) analysis of the dental traumas only 13 . Although there are some minor studies on maxillofacial trauma in some parts of Brazil, this is the first report analyzing data of oral and maxillofacial traumas in the last decade.…”
Section: Introductionmentioning
confidence: 99%